2020
DOI: 10.1101/2020.06.17.20134262
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Outpatient Screening: a Prediction Score for Adverse Events

Abstract: Background. We sought to develop an automatable score to predict hospitalization, critical illness, or death in patients at risk for COVID-19 presenting for urgent care during the Massachusetts outbreak. Methods. Single-center study of adult outpatients seen in respiratory illness clinics (RICs) or the emergency department (ED), including development (n = 9381, March 7-May 2) and prospective (n = 2205, May 3-14) cohorts. Data was queried from Partners Enterprise Data Warehouse. Outcomes were hospitalization, c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 16 publications
0
14
1
Order By: Relevance
“…Data concerning admission BP in patients with COVID-19 are very scarce and are included, at best, as minor pieces of data in larger predictive scores. Two recent studies found an association between worse outcomes and low BP 16 , 17 and 2 others found an association between worse outcomes and high BP. 18 , 19 However, none focused on the capital importance of BP per se.…”
Section: Discussionmentioning
confidence: 96%
“…Data concerning admission BP in patients with COVID-19 are very scarce and are included, at best, as minor pieces of data in larger predictive scores. Two recent studies found an association between worse outcomes and low BP 16 , 17 and 2 others found an association between worse outcomes and high BP. 18 , 19 However, none focused on the capital importance of BP per se.…”
Section: Discussionmentioning
confidence: 96%
“…We found no major difference in the diagnostic yield between resting and ambulatory SaO 2 in this setting. The predictive value of outpatient oxygen saturation values have been previously described (5, 22). One study provided pulse oximeters to participants with COVID-19 who presented to an ED or outpatient testing centers; 29% required subsequent hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, no single oxygen saturation reading alone predicted outcome as there was overlap in both the resting and ambulatory oxygen saturations of those who remained at home and those who were hospitalized. Therefore, pulse oximetry may be most useful as an adjunct to clinical monitoring of high risk populations such as those over 60 years of age, males, and persons with elevated body mass index (5, 23).…”
Section: Discussionmentioning
confidence: 99%
“…A second tool, from the United States, was found to be less sensitive and specific, despite including a greater number of resourceintensive inputs. 21 In the Jiangsu Province of China, Sun et al 22 validated a homegrown system for triaging confirmed COVID-19 patients. The algorithm includes seven inputs: age, blood oxygen saturation, CT scan results, heart rate, lymphocyte count, oxygenation requirements, and respiratory rate.…”
Section: Questionsmentioning
confidence: 99%
“…A total of 25 studies were identified that described triage protocols for COVID-19 patients, 11 of which were from LMICs. There were only two 21 validation studies related to these tools, one of which was from China, 22 an upper-middle–income country. There were 48 severity scoring tools described in the literature, 23 of which were from LMICs.…”
Section: Questionsmentioning
confidence: 99%